Accreditation Sanctions as Quality Signals in a Competitive Market for Students. Issue 6 (September 2022) - Burnett, Christopher A.
Tuition-dependent colleges and universities face increasing competition for students. This study examined whether accreditation sanctions might serve as signals of quality and relate to enrollment. Results of a panel analysis showed enrollment declined for institutions after being placed on sanction with their regional accreditor. Specifically, 4-year private not-for-profit institutions had a 7.7% decline in FTE enrollment 2 years after warning ( p  < .05) and public 4- and 2-year institutions had a 5.5% and an 9.4% relative decline in FTE 2 years after probation, respectively ( p  < .05). Additional results demonstrated that a relationship remained up to 4 years post-sanction.